ANALISIS STRUKTUR NOVEL PUDARNYA PESONA CLEOPATRA KARYA HABIBURRAHMAN EL SHIRAZY - Erlina, Erlina (Ensiklopedia of Journal, 2025)
This research is motivated by a structural analysis of Pudarnya Pesona Cleopatra by Habiburrahman El Shirazy. Structural analysis of a literary work involves identifying, assessing, and describing the functions and relationships among its intrinsic and extrinsic elements. The purpose of this study is to describe the analysis of the novel through a feminist theoretical approach, and to explain the intrinsic and extrinsic elements found in Pudarnya Pesona Cleopatra. This is a qualitative study using a descriptive method. The data consist of quotations from the novel. The data sources are classified into two types: (1) primary data, namely the novel Pudarnya Pesona Cleopatra by Habiburrahman El Shirazy, published by Republika in 2008 (111 pages, seventeenth printing); and (2) secondary data, including books and research papers relevant to this study, which serve to strengthen the arguments and complement the research findings. Data collection techniques include: (1) reading and understanding the novel Pudarnya Pesona Cleopatra by Habiburrahman El Shirazy; (2) coding the text related to the research focus; and (3) recording all data on feminist aspects identified through coding. The steps of data analysis are: (1) reading all collected data; (2) classifying data according to the analytical framework; (3) interpreting the data; and (4) drawing conclusions from the analysis. The results show that this novel strongly reflects the realities of life, helping readers interpret that human love is temporary, while divine love endures beyond this world.Keywords: Structural Analysis, Novel, Feminism, Intrinsic, Extrinsic